The Financial Implications of ESG Performance: Innovation as a Mediator and External Assurance as a Moderator - Shellyane, Elizabeth Agustine; Dharmastuti, Christiana Fara (Universitas Mercu Buana, 2025)
Objectives: Investor and regulator attention to sustainability practices has made Environmental, Social, and Governance (ESG) performance increasingly crucial for companies. This study examines the effect of ESG performance on financial performance with innovation as a mediator and external assurance as a moderator.Methodology: The study was conducted on 58 publicly listed Indonesian companies during the 2023–2024 period that have ESG Risk Rating scores from Morningstar Sustainalytics and have reported research and development expenses in their operations. SEM-PLS aims to analyze the developed model.Finding: The results show that (1) good ESG performance (indicated by a lower ESG Risk Rating) has a significant positive effect on ROE, indicating that better ESG performance is associated with higher financial performance; (2) innovation acts as a mediator, where sustainability practices encourage innovative activities that positively impact financial performance; and (3) external assurance strengthens the relationship between ESG and financial performance through enhanced reporting credibility and reduced information asymmetry..Conclusion: These findings affirm that ESG is not merely about compliance but a strategy to drive innovation and increase profits. The managerial implications include reducing ESG risk through measurable sustainability initiatives, strengthening investment in green research and development, and obtaining independent external assurance to enhance reporting credibility and increase investment opportunities.